CT, MRI, and 18F-FDG PET/CT findings of malignant peripheral nerve sheath tumor of the head and neck. (October 2017) - Kim, Ha Youn; Hwang, Ji Young; Kim, Hyung-Jin; Kim, Yi Kyung; Cha, Jihoon; Park, Gyeong Min; Kim, Sung Tae
Background: Malignant peripheral nerve sheath tumor (MPNST) is a highly malignant tumor and rarely occurs in the head and neck. Purpose: To describe the imaging features of MPNST of the head and neck. Material and Methods: We retrospectively analyzed computed tomography (CT; n = 14), magnetic resonance imaging (MRI; n = 16), and 18 F-FDG PET/CT (n = 5) imaging features of 18 MPNSTs of the head and neck in 17 patients. Special attention was paid to determine the nerve of origin from which the tumor might have arisen. Results: All lesions were well-defined (n = 3) or ill-defined (n = 15) masses (mean, 6.1 cm). Lesions were at various locations but most commonly the neck (n = 8), followed by the intracranial cavity (n = 3), paranasal sinus (n = 2), and orbit (n = 2). The nerve of origin was inferred for 11 lesions: seven in the neck, two in the orbit, one in the cerebellopontine angle, and one on the parietal scalp. Attenuation, signal intensity, and enhancement pattern of the lesions on CT and MRI were non-specific. Necrosis/hemorrhage/cystic change within the lesion was considered to be present on images in 13 and bone change in nine. On 18 F-FDG PET/CT images, all five lesions demonstrated various hypermetabolic foci with maximum standard uptake value (SUVmax ) from 3.2 to 14.6 (mean, 7.16 ± 4.57). Conclusion: MPNSTs can arise from various locations in the head and neck. Though non-specific, a mass with an ill-defined margin along the presumed course of the cranial nerves may aid the diagnosis of MPSNT in the head and neck.